2018
DOI: 10.1177/0957456518801141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of defect-size estimation in taper roller bearing

Abstract: In this article, the estimation of different defect sizes present on the outer race of taper roller bearing confirms the effectiveness of the applied method for different vibration signals. Experiments and numerical model conducted for three primary conditions of bearing setting, which are positive, negative, and zero clearance. The outer race is installed in five different positions so that the defect located at 0°, 45°, 90°, 135°, and 180°. The output of the numerical model finds close correlation with the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…The obtained results have good consistency with that of the Hertzian theory, [20]. The effect of the displacement of inner race and the friction coefficient on fatigue, wear, penetration and generated Hertzian stress was studied, [21]. The contact stress of large diameter ball bearings was studied using analytical and numerical methods, [22].…”
Section: Introduction the Defects And Malfunction Of Mechanical Compo...supporting
confidence: 61%
“…The obtained results have good consistency with that of the Hertzian theory, [20]. The effect of the displacement of inner race and the friction coefficient on fatigue, wear, penetration and generated Hertzian stress was studied, [21]. The contact stress of large diameter ball bearings was studied using analytical and numerical methods, [22].…”
Section: Introduction the Defects And Malfunction Of Mechanical Compo...supporting
confidence: 61%
“…The results showed that, the amplitude level of vibration signals was produced from outer race defect is more than that for the inner race defect [13]. FE Dynamic model considers a suitable method used to diagnosis the bearing defects of different sizes in the bearing, [14].…”
Section: Necessity To Detect and Identify Of Machine Faultsmentioning
confidence: 99%
“…The results showed that, the amplitude level of vibration signals was produced from outer race defect is more than that for the inner race defect [11], [12]. FE Dynamic model considers a suitable method used to diagnosis the bearing defects of different sizes in the bearing [13].…”
Section: Introduction mentioning
confidence: 99%